PEMANFAATAN TEKNOLOGI INFORMASI DAN MEDIA DALAM PEMBELAJARAN FIQIH UNTUK MENINGKATKAN PEMAHAMAN IBADAH DAN KESADARAN MENJALANKAN IBADAH DI UNIVERSITAS NURUL HUDA - Ahmad Sodikin; Fajar Sidik (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2026)
This study aims to analyze the use of information technology and learning media in Fiqh instruction, as well as their contribution to improving students’ understanding of worship and their awareness of performing acts of worship at Nurul Huda University. This study employs a descriptive qualitative approach with data collection techniques including classroom observation, interviews with faculty and students, and document analysis. The results of the study indicate that the use of information technology through interactive presentation media, educational videos, and digital platforms is able to increase student engagement, clarify concepts of worship, and encourage students to practice their religious duties more consistently. The integration of technology-based media also helps lecturers deliver Fiqh material in a more contextual and applicable manner. This study concludes that the utilization of information technology and learning media in Fiqh instruction makes a positive contribution to improving the quality of Islamic Religious Education and needs to be developed continuously within the higher education environment.